ANALISIS KONSEP BLUE ECONOMY PADA SEKTOR KELAUTAN DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2014 TENTANG KELAUTAN - Heltina Wati Sitorus; Zulfikar Jayakusuma; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Indonesia is an archipelagic country. As an archipelagic country, most of the Indonesian people's income comes from the marine sector. Utilization of marine sector by using the concept of blue economy can create sustainable development in Indonesia. Where the blue economy is defined as an economic model that promotes the implementation of sustainable development (sustainability), an economic model that develops marine and fisheries industry that emphasizes growth, job creation, and encourages innovation of environmentally friendly technologies. From the explanation of the archipelago and the blue economy that is being built in Indonesia, of course Indonesia is very profitable in that aspect. However, this still gets doubts and problems such as, first, how is the concept of blue economy in the marine sector within the framework of sustainable development in Indonesia ?. Second, what are the goals and solutions of marine design in Indonesia? Third, is the concept of a blind economy advancing the sustainable development of the marine sector in Indonesia? The purpose of this research is to find out the concept of blue economy in marine sector in the framework of sustainable development in Indonesia and see the sustainable development of marine sector in Indonesia, and to know the shape of the concept of blue economy affects sustainable development of marine sector of Indonesia. The type of research used in this study using normative legal approach method. In this study, the authors conducted a study of the principles of law that started at UNCLOS 1982. From the results of the research, there are three main points that can be concluded, first, the concept of Blue Economy in the marine sector can form the development of the gap in Indonesia. Second, the configuration in sustainable development in Indonesian marine sector is a form of regulation and attention that exists, the government should pay more attention to the marine sector, both policy making and others. Third, the concept of blue economy is maritime sector of Indonesia is still applied in some areas and is expected to be wider than before. Keywords: Blue Economy - Marine Sector - Sustainable Development